2 years older then Marjorie.....m = Marjorie
m + 2 <== ur expression
5y - 2x + 1 = 0.
5y = 2x-1.
y = 2/5 x - 2/5
this tells us that tan(theta) = 2/5
sin(theta)/sqrt(1-sin^2(theta)) = 2/5
x/sqrt(1-x^2)=2/5
x^2/(1-x^2)=4/25
25x^2=4-4x^2
29x^2=4
x^2=4/29
x = -2/sqrt(29) because quadrant III
cos(x) = sqrt(1-4/29) = -5/sqrt(29)
tan(theta)=2/5
cos(theta)=-5/sqrt(29)
sin(theta)=-2/sqrt(29)
cot(theta)=5/2
sec(theta)=-sqrt(29)/5
csc(theta)=-sqrt(29)/2
I think it means check your answer and provide reasoning
Answer: Let x = the length of a side of the square
a2 + b2 = c2
x2 + x2 = 102
2x2 = 100
x2 = 50
x = √50
x = 5√2 cm
Step-by-step explanation: